Students’ and Faculty Perspective about the Challenges in Feedback Process in an Outcome Based Education System - Nida Gulzar Zeb, Kamran Afzal, Ayesha Almas, Syeda Nazia Kulsum, Hemmat H.G.Hareedy, Sawsan Mustafa Abdallah, Waqas Sami (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Effective Feedback process is the running blood for learning in an outcome based teaching system and is a powerful tools for improving the future performance of the medical students. Currently almost all medical institutes seem to grapple with the feedback process but the desired results in form of students’ improvement are not considerable. Keeping in view the aforementioned mismatch a structured evaluation of the challenges in its way is necessary. Objectives: The aim of study was to identify the challenges faced by medical students and faculty in feedback process and to compare the discrepancy between students’ and faculty’s perspective about the factors that impede the process in college of medicine Majmaah University KSA. Materials and methods: This was an observational questionnaire based study conducted in 2020-2021 upon students and faculty of medical college of Majmaah University. The participants filled their response about the barriers they face during the feedback process. The data was scrutinized and analysed on SPSS ver 28. Pearson Chi-square and Fisher Exact tests were applied to compare the different responses between faculty and students. A Bonferroni adjusted p-value was reported for multiple comparisons. A p-value of less than 0.05 was considered as statistically significant. Results: It was found that 62% participants said students are afraid of negative comments, 70 % said that students don’t consider the process important, 72 % said it’s a time consuming process comments. Statistically significant results were found in responses between faculty and students about the four variables namely feedback is not taken important, time consuming, increased work load and language barrier. Conclusions: The most significant hurdles in the process of effective feedback in our setup are uninterested pupils, fear of being judged, weak staff skills, time and work constraints, and a language barrier.